Thyroid Gland Volume Measured by Ultasound in Different Age Groups in Sulaimani Population - Faraj, Faruk Hasan; Saeed, Kamal Ahmad; Muhammad, Dler Abdulruhman (Sulaimani Journal for Pure and Applied Sciences, 2007)
The main objective of this study is to describe thyroid volume measured by ultrasonography in different gender and age groups in the Sulaimani population. In this cross-sectional study, two hundred subjects aged three to seventy five years with healthy thyroids were studied. The sample consisted of five age groups with twenty females and twenty males in each group. Information was collected on age, sex, body height, neck length, neck circumference, and thyroid volume measured by sonography. The results of this study show strong correlations between chronological age, neck circumference, and body length. Sex does not significantly affect the thyroid volume.
Keywords: thyroid gland volume; ultrasound; different age groups